Case Report: Unusual Cause of Chest Pain: A Multi-Image Assessment of a Cardiac Mass - Serrano-Roman, Javier; Saenz-Ancira, Santiago; Armendariz-Ferrari, Jose C.; Fernandez-Badillo, Valente; Solorzano-Pinot, Enrique; Espejel-Guzman, Adrian; Berarducci, Joaquin; Aranda-Fraustro, Alberto; Garcia-Cardenas, Mauricio; Espinola-Zavaleta, Nilda (Frontiers in Cardiovascular Medicine, 2022)
Myxomas represent the most common benign primary cardiac tumor, they usually grow out of the interatrial septum into the left atrium with a pedunculated base. Intracardiac masses can be found incidentally on imaging studies, but symptomatology may arise secondary to the mass effect, embolization, and valvular function impairment. We present the case of a 75-year-old woman who arrived at the emergency department with atrial fibrillation and N-STEMI secondary to a highly vascularized neoplasm visible by coronary angiography and angiotomography. Scarce reports show high quality multi-imaging assessment of significantly vascularized myxomas with such atypical presentation. High-definition imaging studies played a fundamental role in the surgeon's management of a mass with a complex neovascularization.